Aspectos técnicos e ambientais da produção de melão na Zona Homogênea Mossoroense, com ênfase ao controle da mosca-branca e da mosca-minadora - Oliveira, Alan Martins de (Universidade Federal Rural do Semi-Árido, 2008)
This work aims to analyze technical and environmental aspects of the production of melon in the Homogeneous Zone in Mossoró emphasizing the fitosanitary control of the whitefly and Leaf Miner Fly. It is divided in two parts. In the Chapter I, an experiment was installed in Baraúna-RN, using delineation in blocks at random, in pieces subdivided in the time 6 x 5. There were six treatments in the piece: 1-physical control (blanket) chemist; 2-physical control (manta) + natural (oil of neem); 3-physical control (manta) + chemist + natural + peat (oil of neem); 4-physical control (manta) + chemist + peat + biological (trichoderma); 5-chemical control; 6-testifies. There were five times of evaluation in the sub piece of pest infestation: 20°, 28°, 36°, 44° and 52° DAT Days After the transplanting. Quantitative characteristics were analyzed: counting of nymphs and adults of whitefly and, larvae and adults of Leaf Miner Fly; qualitative characteristics in the fruits: mass, soluble solids, pulp firmness and pH. The use of alternative methods: biological, physical, natural control and peat have positive effects when used in the associate form. So, it is possible to reduce the use of pesticides in the melon. In the Chapter II, it was used like methodological proceedings the exploratory and descriptive search. There were valued data of questionnaires devoted to the owners or managers of the producing enterprises of melon, through probabilistic sample. It was checked that the short cycle of the culture, the model based on the monoculture, the agricultural mechanization, the elevated consumption of energy and the use of pesticides and chemical fertilizers associated to the marketing demands of qualitative and quantitative characteristics of the results, are affecting the sustainability of the culture of melon. In the final considerations, we realize that the technologies and the developed methods of production, aiming to pay attention to the growing demand of the result, especially of the rich countries, are untenable in the environmental optics; besides proposing larger searches aiming the sustainability: economical growth with ecological care and social equity
Technical and environmental aspects of the production of melon in the Homogeneous Zone in Mossoró, emphasizing the control of the Whitefly and Leaf Miner Fly
Keywords: Bemisia tabaci; Liriomyza sp; Control methods; Sustainability; Bemisia tabaci; Liriomyza sp; Métodos de controle; Sustentabilidade; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA